Social responsibility in institutions and its role in supporting governance to achieve sustainability - Daoudi, Merouane (The International tax journal, 2025)
The study aims to demonstrate the role of social responsibility as a fundamental element in achieving good governance and institutional sustainability, as it is not limited to voluntary initiatives but includes institutions' commitment to practices that enhance transparency, accountability, and sustainable development. Integrating social responsibility into governance policies contributes to improving the institution's reputation, attracting investors, and enhancing financial and social performance, it also helps achieve sustainability by reducing environmental risks, improving working conditions, and promoting social justice, however, institutions face challenges such as high costs, weak legal frameworks, and a lack of institutional awareness, accordingly, achieving integration between social responsibility and governance requires regulatory reforms, developing sustainable policies, and motivating companies to adopt social responsibility standards to ensure long-term economic, social, and environmental sustainability.